Aktywna polityka rynku pracy na przykładzie powiatowego programu przeciwdziałania bezrobociu i aktywizacji lokalnego rynku pracy w latach 2003-2006 dla miasta Łodzi - Kalisiak-Mędelska, Magdalena (The Active Policy of Labour Market - the Case of the Prevention of Unemployment Program in the City of Łódź, 2005)
This article presents the way the local authorities in Łódź carry out the policy of local labour market. To achieve this aim author uses the acts of local law and describes tasks the local government must complete in this area.Local development is defined as a process of permanent changes. There are many factors which have the influence on dynamics and quality of this process. Unemployment seems to be the most complicated among them. It forces local governments to create very original programs which help them to struggle with this problem.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 406-418